The Analysis of Science Literacy Ability and Teachers' Capability in Implementation of Learning by Science Literacy Oriented in Islamic Kindergarten at Bangko City - Siti Aisyah; Minnah El Widdah; Sukarno Sukarno (Jurnal Penelitian Pendidikan IPA, 2021)
This study aims to determine the analysis of scientific literacy skills and the ability of teachers in developing science literacy-oriented learning in Islamic Kindergartens in Bangko City. This study uses a quantitative approach with survey techniques. Data analysis was carried out by means of quantification on each measured aspect and continued with descriptive analysis. Based on the data and discussion as described above, at the end of this study it can be concluded that in general the ability of Islamic Kindergarten teachers in Bangko City is evenly distributed in each category. The scientific literacy ability of teachers with category "A" is 8 people or about 22.22%. There are 9 teachers with literacy ability categories "B" and "C" each or about 25%, while the rest, as many as 10 people or around 27.78% are categorized as "D". In the aspect of teacher ability in developing science literacy-based learning, it is dominated by teachers with the ability category "D", as many as 12 people or about 33.33%, then followed by teachers with category "B" abilities as many as 10 people or about 27.27%. In the third place are teachers with the ability category "C" as many as 9 people or about 25%, and the rest are teachers group with category "A", which is as many as 5 people or about 13.89%. Therefore, the improvement and development of teachers' scientific literacy skills still needs to be improved